Kendala dan Strategi Guru PJOK Dalam Mengajarkan Tenis di SD Global Surya Islamic School Bandar Lampung - Alifia Ramadhina; Maghribi, Inosen Lingsir; Ariestika, Elsa (Indonesia Sport Journal, 2025)
This study aims to describe the challenges faced by Physical Education, Sports, and Health (PJOK) teachers and the strategies implemented in teaching tennis at SD Global Surya Islamic School Bandar Lampung SD Global Surya Islamic School Bandar Lampung. A descriptive qualitative approach was employed, using observation, interviews, and documentation as data collection techniques. The research subjects included the PJOK teacher and students from grades IV to VI. Data analysis involved data reduction, data display, and conclusion drawing. The results revealed several key obstacles in tennis instruction, including limited facilities and equipment, students' lack of prior knowledge of basic tennis techniques, restricted instructional time, and the absence of specialized training for teachers in tennis instruction at the elementary level. Despite these challenges, the PJOK teacher applied various adaptive strategies such as modifying learning tools, implementing simplified game-based activities, using demonstration and repetitive practice methods, applying small group learning, and collaborating with parents and the school committee. These strategies reflect the teacher’s creativity in delivering engaging and contextualized lessons despite constrained conditions. This study contributes to the development of effective teaching models for physical education, particularly in teaching tennis in elementary schools with limited resources. The findings are expected to inform schools and policymakers in designing support programs that enhance physical education through practical and innovative approaches.